1977
DOI: 10.1038/bjc.1977.172
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cell-surface glycoproteins of rat hepatomas and embryonic rat liver

Abstract: Summary.-Cell-surface glycoprotein of 3 rat hepatoma strains and late-embryonic liver was metabolically labelled in vivo with [3H]-or [14C]-fucose. Trypsinization of the cells and exhaustive pronase digestion of combined hepatoma-liver trypsinates followed by gel filtration over Sephadex-Biogel mixtures, yielded elution profiles that contained more early-eluting (high-mol.-wt.) glycopeptides for hepatomas than for liver. At least 3 factors were identified which acted to augment the fraction of earlyeluting tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…5) expose fast-eluting fucosyl glycopeptides when compared with stationary B and T lymphocytes respectively. From these and earlier results (Van Beek et al, 1977a, 1979a and from the results of De Leij et af. (ms. submitted) we may conclude that growth as such is not instrumental in the generation of the fast-eluting glycopeptides.…”
Section: Discussionsupporting
confidence: 72%
“…5) expose fast-eluting fucosyl glycopeptides when compared with stationary B and T lymphocytes respectively. From these and earlier results (Van Beek et al, 1977a, 1979a and from the results of De Leij et af. (ms. submitted) we may conclude that growth as such is not instrumental in the generation of the fast-eluting glycopeptides.…”
Section: Discussionsupporting
confidence: 72%
“…These enzymes are probably involved in the synthesis of linear and branched polylactosaminoglycans and p6-GlcNAc-containing mucin core structures, respectively. Like many other malignant cells [3 -71, Novikoff cells have been reported to express cell-surface glycans of higher molecular mass relative to those present in their normal counterpart (embryonic rat liver) [26]. In view of the specificities of the GlcNAc transferases [ l l , 13, 18, 25, 271 it might be predicted that the N-linked cell-surface glycans of Novikoff cells are predominantly of the bisected type and contain only few lactosaminoglycan elongations, whereas the 0-linked chains contain N-acetyllactosamine repeats in linear or branched chains that are attached to Ga1/31+3(GlcNAc/31 j6)GalNAc and GlcNAcfll 4 3(GlcNAc/31+6)GalNAc much cores.…”
Section: Resultsmentioning
confidence: 99%
“…2 values (Table 2) revealed that its structure was that shown for oligosaccharide bis-tri ( at a probe temperature of 300 K. Chemical shifts are expressed downfield from internal sodium 4,4-dimethyl-4-silapentane-1-sulfonate, but were actually measured by reference to internal acetone (6 = 2.225 ppm) with an acuracy 0.002 pprn. The numbering of the residues is according to the system used in [26].…”
Section: Resultsmentioning
confidence: 99%
“…Our observations of the decrease in ConA-binding activity and increase in sialylation of the glycoproteins in the ZAH cells are similar to those made earlier in different transformed cell systems, including HCC. 16,25,29 The increase in sialylation of the membrane glycoproteins upon transformation has mainly been attributed to increased branching of N-linked glycoproteins; 8 however, gp120 in ZAH appears to be an O-linked oligosaccharide as it does not bind to LCA or PHA-P, although ZAH C membranes contain at least one specific fucose-containing N-linked complex-type sialoglycoprotein also. The presence of sialylated O-linked and N-linked glycoproteins, as observed in our system, has also been reported in a number of rat ascites HCC 27,30 and in Novikoff HCC.…”
Section: Identification and Characterization Of Tumor-specific Glycopmentioning
confidence: 99%